2011
DOI: 10.1104/pp.111.181057
|View full text |Cite
|
Sign up to set email alerts
|

Structural Resolution of the Complex between a Fungal Polygalacturonase and a Plant Polygalacturonase-Inhibiting Protein by Small-Angle X-Ray Scattering  

Abstract: We report here the low-resolution structure of the complex formed by the endo-polygalacturonase from Fusarium phyllophilum and one of the polygalacturonase-inhibiting protein from Phaseolus vulgaris after chemical cross-linking as determined by small-angle x-ray scattering analysis. The inhibitor engages its concave surface of the leucine-rich repeat domain with the enzyme. Both sides of the enzyme active site cleft interact with the inhibitor, accounting for the competitive mechanism of inhibition observed. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 60 publications
(86 reference statements)
4
48
0
1
Order By: Relevance
“…S1). Previous work demonstrated that FpPG and PvPGIP2 can be specifically cross-linked by formaldehyde in vitro as a heterodimeric complex (33,35). In vitro cross-linking of the purified PGIP-PG chimera resulted in complexes ranging from homodimers (∼160 kDa) to homotetramers (∼320 kDa), supporting the conclusion that the fusion protein is able to establish intermolecular interactions (Fig.…”
Section: Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…S1). Previous work demonstrated that FpPG and PvPGIP2 can be specifically cross-linked by formaldehyde in vitro as a heterodimeric complex (33,35). In vitro cross-linking of the purified PGIP-PG chimera resulted in complexes ranging from homodimers (∼160 kDa) to homotetramers (∼320 kDa), supporting the conclusion that the fusion protein is able to establish intermolecular interactions (Fig.…”
Section: Resultssupporting
confidence: 57%
“…To circumvent this problem, a chimeric protein in which PvPGIP2 and FpPG were linked by three alanine residues was engineered. Although this linker is too short to permit intramolecular enzyme-inhibitor interactions (33), it should allow intermolecular interactions between the PGIP and PG moieties (Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This noncompetitive inhibition was also observed for PGIP2 and AnPGII (Spinelli et al 2009). In contrast, for PGIP2/FmPG combination, a competitive inhibition was observed and binding of PGIP2 takes place at the active site of the FmPG (Federici et al 2001;Maulik et al 2009;Benedetti et al 2011). While this makes a general consensus more difficult, it emphasizes the complex nature of these systems and the need for independent evaluation of each enzymeeinhibitor pair.…”
Section: Dpmsmentioning
confidence: 54%
“…A number of specific amino acids of PGIP have been proposed to be involved in the binding to EPGs (Stotz et al 1999;Leckie et al 1999;Di Matteo et al 2003). Conflicting models of the architecture of the EPG/PGIP complex have been proposed, and there has been a significant amount of confusion surrounding what type of inhibitor PGIP is, a competitive, a noncompetitive or a mixed inhibitor (Abu-Goukh & Labavitch 1983;Lafitte et al 1984;Barmore & Nguyen 1985;Johnston et al 1993;Stotz et al 1999;Federici et al 2001;James & Drubery 2001;King et al 2002;Barnes 2004;Sicilia et al 2005;Spinelli et al 2009;Maulik et al 2009;Benedetti et al 2011). Previous studies in our laboratory have shown PGIP2 to be resistant to hydrolysis by pepsin under conditions that readily digest EPGs (King et al 2002).…”
Section: Dpmsmentioning
confidence: 98%